Holes and cracks in rigid foam films. (11th June 2015) - Petit, P. C.; Le Merrer, M.; Biance, A.-L.
Abstract : The classical problem of foam film rupture dynamics has been investigated when the film interfaces exhibit very high rigidity due to the presence of specific surfactants. Two new features are reported. First, a strong deviation from the well-known Taylor–Culick law is observed. Second, crack-like patterns can be visualized in the film; these patterns are shown to appear at a well-defined film shrinkage. The key role of surface-active material on these features is quantitatively investigated, pointing to the importance of surface elasticity to describe these fast dynamical processes and thus providing an alternative tool to characterize surface elasticity in conditions extremely far from equilibrium. The origin of the cracks and their consequences on film rupturing dynamics are also discussed.